Claims on intangible property as a matrimonial property : an analysis of the law in Malaysia and Shariah - Sacko, Alhassane Sekou
Matrimonial property disputes are one of the areas of law that is highly litigated in Shariah courts. Claims on tangible interests are common and generally do not raise complex issues. However, when it comes to distribution of interest in intangible property such as profits in long term investment, rights in intellectual property and rights in increase of future earnings, many legal issues may arise, such as the locus standi of the claimants to take legal action on the future interests and how should the court divide the intangible property as a matrimonial property. The Shariah courts in Malaysia have been adopting the general approach of fairness and justice as well as honoring mutual domestic agreement to determine spouses' rights in personal matrimonial property, but it is unclear if the courts would adopt the same approach in cases involving future interest. This research investigates and examines the scope of intangible property under the Malaysia laws and under the Shariah. This research also examines whether intangible property could be claimed as matrimonial property and how should it be distributed as matrimonial property. This research applied doctrinal analysis research methodologies which involved analyzing the legal principles in Malaysia and the principles oi fiqh; to identify whether the Malaysian law and Shariah recognized intangible interests as a matrimonial property. This research also applied comparative analysis between the laws applicable in Malaysia and under Shariah for intangible interest with special reference to principles on intellectual property and increase in hwnan earnings. The study found that laws in Malaysia and Shartali recognize the concept of intangible property as one of the types of property, and therefore it can be claimed as part of matrimonial property in the Shariah court. The study also found that the Shariah Court can apply the "contribution test" which is the general legal principle used by the courts to determine the division of intangible assets as matrimonial property. This study also proposes that the Shariah Court to take into account the principle of" interest of the children" as one of the factors required in the division of intangible assets as matrimonial property. This finding is important as it introduces a new paradigm in the jurisdiction of the Shariah Courts and allows Shariah Courts to develop and to cater the changing lifestyles of today's society. This study found that intangible assets are recognized by the laws of Malaysia and Shariah as one of the types of property that can be claimed as matrimonial property, and the general legal principles used for tangible assets to determine and divide assets as matrimonial property can be used by the Shariah courts for the division of intangible assets as matrimonial property.